De-escalating adjuvant therapy after pathologic complete response in oral squamous cell carcinoma: Chemoradiotherapy benefits only high-risk subgroups - Yang, Yanjie; Liu, Yanyan; Yang, Man; Fan, Yunli; Du, Wei (Frontiers in Oncology, 2025)
BackgroundThe optimal adjuvant therapy for oral squamous cell carcinoma (SCC) patients achieving pathological complete response (pCR) after neoadjuvant immunochemotherapy (NAIC) remains uncertain. While radiotherapy (RT) and chemoradiotherapy (CRT) improve locoregional control, their comparative efficacy and toxicity profiles in this setting are poorly defined.MethodsOral SCC patients with pCR post-NAIC were retrospectively enrolled and stratified into RT and CRT groups. Propensity score matching balanced baseline characteristics. Outcomes included 3-year locoregional control (LRC), overall survival (OS), and toxicity. Subgroup analyses evaluated treatment effects by radiologic extranodal extension (rENE) and tumor differentiation.ResultsAmong 116 patients analyzed (84 matched), CRT showed no significant LRC or OS benefit over RT alone in the overall cohort (LRC: HR 1.89, 95% CI 0.26–4.72, p=0.625; OS: HR 1.45, 95% CI 0.62–3.41, p=0.392). However, subgroup analyses revealed CRT improved outcomes in high-risk patients (rENE+ or poorly differentiated tumors), reducing recurrence by 50% (rENE+: HR 3.12, 95% CI 1.13–8.60, p=0.028; poor differentiation: HR 3.45, 95% CI 1.23–9.68, p=0.019) and enhancing 3-year OS (rENE+: 62.4% vs. 50.1%, p=0.036; poorly differentiated: 68.3% vs 53.8%, HR 2.88, p=0.022). CRT was associated with significantly higher acute and chronic toxicities (Grade 3–5 mucositis: 36.0% vs. 12.1%).ConclusionCRT should be reserved for high-risk pCR patients (rENE+ or poorly differentiated tumors), while RT alone suffices for low-risk cases. This risk-adapted approach optimizes outcomes while minimizing toxicity.